Distance Learners' Satisfaction Towards Information Technology Usage - Abu Mansor, Nur Naha (1998)
The study focuses on learners' satisfaction towards IT usage in DE programmes. The first objective is to determine the satisfaction level of learners towards Internet and WWW Usage in terms of facilities, presentation mode and support services provided. Secondly, it determines the difference in learners' satisfaction level towards Internet and WWW usage with learner background in the various aspects of ethnic group, gender, organisation, professions, computer experience, educational achievement and computer background. The size of sample was 74 respondents from the population of 140 learners of IDEAL. Data were collected using self-administered questionnaires were given to respondents in one of their face-to-face meetings with their lecturers in Universiti Putra Malaysia. Results showed that respondents' satisfaction level on the overall usage of IT in their learning was said to be of moderate satisfaction. Specifically, however, in relation to facilities provided in the program, it was rated as moderate satisfaction. There were some aspects of the facilities such as the availability of registration and scheduling facilities of on-line tutorial and modules for learners and the need of back-up servers as these aspects are very important in the running of their program. The second component which is presentation mode showed that respondents were also moderately satisfied with the way materials were presented. It was found that several improvements could be made in terms of having up-dated on-line help tools, attachments of study references and having more colourful presentation of materials which could attract learners. As for support services, it was quite difficult to see learners' perception on this, but it could be concluded that as overall, respondents were also moderately satisfied with the current system. Nevertheless, with quicker response time and availability of back-up sites would improve the current situation of the program. For the second objective, the study showed that there was no difference in learners' satisfaction level of IT usage towards the aspects of facilities, presentation mode and support services provided from the various characteristics of learners.